Steel fibre reinforced concrete for prestressed hollow core slabs - Paine, Kevin Andrew (1998)
An investigation of prestressed concrete containing steel fibres as secondary reinforcement to improve performance in shear, flexure and bond is reported. Emphasis is placed on the use of steel fibres in prestresssed extruded hollow core slabs, since these common precast elements have intrinsic difficulty in incorporating traditional secondary reinforcement due to their unique shape and manufacturing method.